CONSTRUCTION PROJECT DELAY DUE TO THE COVID-19 PANDEMIC - S. N, Zanuar; S.R, Mohd Nasir (Journal of Surveying, Construction and Property, 2022)
The COVID-19 pandemic that hit the whole world has harmed several industries including the construction industry. It has caused the operation of the construction industry had to be stopped for a while because the construction industry is reported to be one of the industries with a high risk of COVID-19 virus transmission. Due to that, many construction projects were delayed as a result of series of movement control orders by the government. The purpose of this study is to identify the main contributor factors to project delay due to Covid-19. In addition, this study identifies the mitigation actions to overcome the delays for building construction project in Malaysia. Quantitative method was used and online questionnaire survey were distributed to the target respondents involves clients, consultants, and contractors. The research area covers the conurbation of Klang Valley, Great Penang, and Iskandar city as these areas contain about a third of the overall country’s population (Chin et al., 2019). In addition, the number of construction companies as at March 2021 located in Klang Valley, Johor and Penang are 1672, 653 and 323 respectively (CIDB, 2021). Relative Important Index (RII) and correlation analysis were used to analyse the data obtained from the survey. The finding of this study identifies the main factors contribute to delay during COVID-19 pandemic are delay in material delivery; delay in decision making by the consultants; delay in revising and approving document; and unclear of Standard of Procedure (SOP) instructions by the government. As a result, project is suffering with cost overrun and the loss of skilled and unskilled labours. In order to overcome delay, the findings suggest that proper planning and rescheduling; systematic and clear communication; getting help from government aid and completing worker’s overdue payment are among the mitigation actions proposed by the respondents. The finding of this study shed light in preventing unnecessary delays in construction project due to the unpredictable pandemic by identifying the factors and impact of delays to improve the awareness of pandemic effect to the construction project. The outcome of the research study can be used as a guidance to help the construction practitioners especially for the clients, consultants, and contractors to monitor and act in the future construction activities to avoid unnecessary project delays when facing unpredictable pandemic in the future.